Development and performance evaluation of modular RC-based power supply for micro-EDM - Wan Azhar, Wan Ahmad; Saleh, Tanveer (2019)
One of the demanding manufacturing processes nowadays is Micro-EDM. Micro-EDM stands for Micro Electrical Discharge Machining. A low discharge energy per pulse is important to achieve micro-level machining by controlling parameters such as gap voltage and type of power supply. Furthermore, developing a Micro-EDM machine is time-consuming and complex. Generally, the power supply unit is built along with the development of the EDM machine and it is not sold separately in the market. Therefore, the purpose of this research is to develop and evaluate a modular power supply unit that is compatible with any EDM or CNC machine for micromachining. The power supply unit is based on Resistor-Capacitor (RC) power supply with the options to vary the output voltage and the capacitance value. In addition, the current is monitored using micro-controller ATmega328p to provide options for short circuit current detection levels. A prototype of a Micro-EDM machine is built for the evaluation of the power supply. Performance evaluations of the power supply are conducted with through-holes drilling by studying the machining time, MRR, diametrical overcut and taper angle with a different variation of gap voltage, RC’s capacitance, and short circuit current detection level. The evaluation results show that the power supply is capable to perform Micro-EDM machining. The power supply can deliver power up to 360 W. During the discharging, the peak current is recorded to spike up to 7A. The discharge energy per pulse can easily be controlled by changing the output voltage and the RC’s capacitance. It is found that at lower discharge energy per pulse, the peak current is lower resulting improvement in MRR, diametrical overcut and taper angle at cost of longer machining time. Furthermore, short circuit current detection level results indicate that machining time is reduced by approximately 5 minutes for every 20 percent increase of the detection level.